Combined Effects of Low-Dose Kanamycin and Noise Exposure on Auditory Brainstem Response and Cochlear Microphonic Potential in Guinea Pigs: Synergistic Effects of Noise and Kanamycin on Auditory Brainstem - Oroei, Mahbobeh; Akbari, Mehdi; Zarrabi, Morteza (Iranian Journal of Child Neurology, 2026)
Objectives: Aminoglycoside‑induced ototoxicity is a well‑recognized adverse effect that commonly presents as sensorineural hearing loss. This study investigated hearing damage by administering two doses of Kanamycin, with or without concurrent noise exposure. Auditory function was assessed using auditory brainstem response and cochlear microphonic potential. Materials & Methods: Guinea pigs were divided into six groups: Control, Noise exposure, Kanamycin 300 mg/kg alone (low dose), Kanamycin 300 mg/kg + Noise, Kanamycin 500 mg/kg alone (high dose), and Kanamycin 500 mg/kg + Noise. Auditory threshold shifts were evaluated using click and pure tones at 4, 6, 8, 12, and 16 kHz. The cochlear microphonic amplitude was measured before and after intervention in the study groups. The latency and amplitude of waves I and III were analyzed in the groups without sensorineural hearing loss. Results: Auditory threshold shifts were significantly greater in the low-dose Kanamycin + noise group compared to both the low-dose Kanamycin alone and the noise-only groups across all stimuli (p < 0.05). In contrast, the high-dose Kanamycin alone and the high-dose Kanamycin + noise groups exhibited similar thresholds. They demonstrated significantly higher thresholds than the noise-only group (p < 0.05). Furthermore, no significant difference in the cochlear microphonic amplitude was found among the study groups. Conclusion: Kanamycin at low doses is not inherently ototoxic; however, when combined with noise exposure, it produces a synergistic effect resulting in severe hearing loss. In this model of auditory damage, cochlear microphonic measurements are less informative than auditory brainstem response testing, providing a more reliable assessment of both peripheral and central auditory pathway function.